Functional organization of human auditory cortex: Investigation of response latencies through direct recordings - Nourski, Kirill V.; Steinschneider, Mitchell; McMurray, Bob; Kovach, Christopher K.; Oya, Hiroyuki; Kawasaki, Hiroto; Howard, Matthew A. (NeuroImage (Orlando, Fla.), 2014)
The model for functional organization of human auditory cortex is in part based on findings in non-human primates, where the auditory cortex is hierarchically delineated into core, belt and parabelt fields. This model envisions that core cortex directly projects to belt, but not to parabelt, whereas belt regions are a major source of direct input for auditory parabelt. In humans, the posteromedial portion of Heschl's gyrus (HG) represents core auditory cortex, whereas the anterolateral portion of HG and the posterolateral superior temporal gyrus (PLST) are generally interpreted as belt and parabelt, respectively. In this scheme, response latencies can be hypothesized to progress in serial fashion from posteromedial to anterolateral HG to PLST. We examined this hypothesis by comparing response latencies to multiple stimuli, measured across these regions using simultaneous intracranial recordings in neurosurgical patients. Stimuli were 100 Hz click trains and the speech syllable /da/. Response latencies were determined by examining event-related band power in the high gamma frequency range. The earliest responses in auditory cortex occurred in posteromedial HG. Responses elicited from sites in anterolateral HG were neither earlier in latency from sites on PLST, nor more robust. Anterolateral HG and PLST exhibited some preference for speech syllable stimuli compared to click trains. These findings are not supportive of a strict serial model envisioning principal flow of information along HG to PLST. In contrast, data suggest that a portion of PLST may represent a relatively early stage in the auditory cortical hierarchy. •We measured latencies of responses to sounds in multiple auditory cortical regions•Earliest responses were found in posteromedial Heschl's gyrus (HG) (auditory core)•Anterolateral HG was characterized by the longest latencies•Posterolateral superior temporal gyrus (PLST) had intermediate latencies•Part of PLST may represent a relatively early stage in auditory cortical hierarchy